High-toughness wear-resistant nylon material for rails and preparation method of high-toughness wear-resistant nylon material
By adding core-shell toughening agent to the nylon material for rails and changing its crystal structure, the problems of insufficient impact resistance, tensile strength and wear resistance of nylon materials are solved, and higher performance indicators and a wider application range are achieved.
Patent Information
- Application Number
- CN202411781955.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The impact resistance, tensile strength and wear resistance of existing nylon materials for rails are insufficient, and cannot meet the requirements of high-speed rail operating speed and load-bearing capacity.
By adding core-shell toughening agent, the crystal structure and shape of nylon material can be changed, and its impact resistance, tensile strength and wear resistance are improved.
It significantly improves the impact resistance and tensile strength of nylon materials, enhances its wear resistance in friction environments, and expands its application range.
Smart Images

Figure BDA0005172987610000061 
Figure BDA0005172987610000062
Abstract
Description
Technical Field
[0001] The invention relates to the field of nylon materials, and in particular to a high-strength, toughness, and wear-resistant nylon material for rails and a preparation method thereof. Background Art
[0002] In modern railway transportation systems, the quality and stability of track laying are directly related to the safety and efficiency of train operation. Among the many components of track laying, nylon fasteners, insulating blocks that hold the rails, and track baffles have become one of the key factors to ensure the normal operation of railways due to their unique performance and important role.
[0003] As an efficient and high-volume mode of transportation, railway transportation has extremely high requirements for tracks. The tracks must not only withstand the huge weight of the train and the impact caused by high-speed operation, but also maintain precise geometry and position to ensure the smooth travel and guidance of the train. Under such harsh conditions, the role of fasteners is particularly important. The nylon fasteners used in track laying are used to lock the casing of the rails, which are made of nylon. While playing its fixing role, this nylon casing must also meet a series of strict performance standards. The modification, strengthening and toughening of the nylon material allows the casing to remain strong and stable when it withstands the huge pressure and impact brought by the rails, and it is not easy to deform or damage. The insulating block that buckles the rails is also made of nylon. The insulating block must not only ensure the electrical insulation performance of the rails and prevent abnormal conduction of current, but also be able to withstand the vibration and friction of the rails during operation. In order to achieve good insulation effect, nylon materials need to have excellent insulation properties and wear resistance.
[0004] In addition, the gauge baffle that controls the track from shifting left and right is also made of nylon. The stability of the track gauge is crucial to the safe operation of the train. The gauge baffle must be able to accurately limit the displacement of the track to ensure that the train runs smoothly on the track. This requires that the nylon material has sufficient strength and toughness, and can also maintain stable performance for a long time without being affected by external environmental factors.
[0005] In the design and manufacture of these nylon fasteners, the volume resistance requirement is also an aspect that cannot be ignored. Because in some cases, telecommunications need to be transmitted through rails, and the volume resistance characteristics of the fasteners will directly affect the transmission quality and stability of telecommunications signals. If the volume resistance of the fasteners does not meet the standards, it may cause attenuation, distortion or even interruption of telecommunications signals, thus affecting the normal operation of the entire railway communication system.
[0006] The research and development of nylon materials is a comprehensive subject, involving the complex relationship between the composition, structure and performance of the material. In terms of material composition, it is crucial to select appropriate reinforcing fibers and additives. Polyamide fiber, as a high-strength fiber material, can significantly improve the strength and toughness of nylon. Glass fiber has excellent mechanical properties and high temperature resistance, and its addition can further enhance the mechanical properties of nylon. However, relying solely on fiber reinforcement cannot fully meet the performance requirements of high-speed rail sleeper covers, and other functional additives need to be added. The introduction of long-chain linear polyamide can improve the crystallization properties and toughness of nylon. By adjusting the content and molecular weight of long-chain linear polyamide, the molecular chain structure of nylon can be optimized, and its flexibility and impact resistance can be improved.
[0007] In terms of preparation methods, how to evenly disperse various raw materials in the nylon matrix and achieve good interface bonding is the key to obtaining high-performance and high-strength nylon materials. Commonly used methods include twin-screw extrusion and injection molding. During the processing, process parameters such as temperature, pressure, and screw speed need to be strictly controlled to ensure the stability of the material's performance and quality.
[0008] In addition to the performance of the material itself, the use environment of the rails also places special requirements on the material. High-speed rail lines are usually exposed to outdoor environments and are subject to different climatic conditions, such as high temperature, low temperature, humidity, ultraviolet radiation, etc. These environmental factors may cause the performance of nylon materials to deteriorate, such as reduced strength, aging and embrittlement. Therefore, high-strength nylon materials also need to have good weather resistance and aging resistance.
[0009] At present, the research on high-strength and wear-resistant nylon materials for rails is still in-depth at home and abroad. Some advanced technologies and methods, such as nanotechnology and composite materials technology, are being introduced into the research and development of materials. The addition of nanomaterials can further improve the performance of nylon, such as enhancing its mechanical properties, improving its thermal conductivity and electrical conductivity, etc. Composite materials technology can combine nylon with other high-performance materials to achieve complementary advantages and develop more innovative pillowcase materials.
[0010] However, despite certain achievements in the research and development of high-strength and toughness nylon materials, there are still some challenges. For example, how to further improve the comprehensive performance of the material to meet the requirements of the ever-increasing running speed and load-bearing capacity of high-speed rail; how to reduce the cost of the material and improve its economy in large-scale applications; how to achieve green and environmentally friendly production and sustainable development of the material, etc. These issues require scientific researchers and engineering technicians to continuously explore and innovate to promote the development and application of nylon materials for rails.
[0011] In view of the problems existing in the prior art, the present application aims to solve the problem that nylon materials have insufficient impact resistance, tensile strength and wear resistance. Summary of the invention
[0012] Purpose of the invention: The purpose of the present invention is to provide a high-strength and wear-resistant nylon material for rails and a preparation method thereof. By adding a core-shell toughening agent, the crystal structure and morphology of the nylon material are changed, thereby improving the impact resistance, tensile strength and wear resistance of the nylon material.
[0013] The technical solution of the present invention:
[0014] The invention discloses a high-strength and tough wear-resistant nylon material for rails, characterized in that the raw materials of the high-strength and tough wear-resistant nylon material for rails include, by weight percentage, 30-50% of polyamide fiber, 10-18% of long-chain linear polyamide, 30-40% of glass fiber, 2-8% of core-shell toughening agent, 1-3% of anti-shrinkage cavity additive, 1-2% of flow agent, 0.5-1.5% of nucleating agent and 0.1-0.5% of antioxidant.
[0015] Furthermore, the raw materials for preparing the core-shell toughening agent include a shell material and a core layer emulsion; the shell material is polymerized by 3-benzoyl-N-vinylpyrrolidone under the action of an initiator.
[0016] Furthermore, the raw materials for preparing the core layer emulsion include: aminoalkyl acrylate, acryltrimethoxysilane, benzoyl peroxide, organic additives, and deionized water.
[0017] The preparation of the shell material comprises the following steps:
[0018] S1: Add 3-benzoyl-N-vinylpyrrolidin-2-one and a certain amount of ethyl acetate into a four-necked flask, and stir in a constant temperature water bath to dissolve them;
[0019] S2: After dissolution, hydrogen peroxide and an initiator are added, the temperature is raised to 50-80°C, and then the reaction is carried out under a nitrogen atmosphere for 2-4 hours;
[0020] S3: After the reaction is completed, the reaction mixture is cooled and filtered, and the insoluble matter is placed in a vacuum drying oven for vacuum drying to obtain a shell material.
[0021] Furthermore, the added amount of the initiator is 0.3-0.5% of the mass of 3-benzoyl-N-vinylpyrrolidone; and the initiator is azobisisobutyronitrile.
[0022] The preparation of the nuclear layer emulsion comprises the following steps:
[0023] S1: Add weighed aminoalkyl acrylate, acryltrimethoxysilane and benzoyl peroxide into a four-necked flask, stir evenly to obtain a premix for later use;
[0024] S2: Take another four-necked flask, add an organic additive, stir evenly, heat to 90°C to 100°C, then slowly add the premix prepared in step S1 to the organic additive and deionized water, and keep the temperature to react for 2 to 4 hours;
[0025] S3: After the reaction is completed, cool the mixture and adjust the pH value to 6-7 to obtain a core layer emulsion.
[0026] Furthermore, the added amount of benzoyl peroxide is 1 to 1.5% of the total mass of aminoalkyl acrylate and acryltrimethoxysilane.
[0027] Furthermore, the amount of the organic additive is 20-40% of the total mass of aminoalkyl acrylate and propenyltrimethoxysilane; and the organic additive is sodium dodecylbenzene sulfonate.
[0028] The preparation of the core-shell toughening agent comprises the following steps:
[0029] S1: adding the shell layer material into a four-necked flask, and then adding the core layer emulsion, sodium dodecyl sulfate, and deionized water, stirring and reacting at room temperature for 1 to 2 hours to obtain a core-shell copolymer emulsion;
[0030] S2: Add sodium chloride to the core-shell copolymer emulsion prepared in S1, stir and demulsify, then wash, separate and dry to obtain a core-shell toughening agent.
[0031] Furthermore, the mass ratio of the shell layer material to the core layer emulsion is 1:2-4.
[0032] The present invention also provides a method for preparing a high-strength, tough and wear-resistant nylon material for rails, which is characterized in that it comprises the following steps: mixing polyamide fiber, long-chain linear polyamide, core-shell toughening agent, anti-shrinkage cavity additive, flow agent, nucleating agent and antioxidant, adding the mixture to the main feeding port of a twin-screw extruder, melt mixing, adding glass fiber to the side feeding port of the twin-screw extruder, mixing, extruding and granulating to obtain the high-strength, tough and wear-resistant nylon material for rails.
[0033] The rubber core in the core-shell structure has good elasticity and deformation ability. When the nylon material is impacted, the core-shell toughening agent can absorb and disperse the impact energy, thereby reducing stress concentration and reducing the possibility of material rupture. The presence of the rubber core can trigger the formation of silver streaks and shear bands. The generation and development of silver streaks can consume a lot of energy, while the shear band helps to prevent the expansion of cracks and improve the toughness and impact resistance of nylon materials. The shell layer usually has good compatibility with the nylon matrix, which can promote the uniform dispersion of the toughening agent in the nylon and enhance the interfacial bonding. Good interfacial bonding helps to effectively transfer stress between the nylon matrix and the toughening agent, improving the overall performance of the material. The presence of the core-shell toughening agent also induces the crystallization behavior of nylon, changes the crystal structure and morphology, and thus improves the strength and rigidity of nylon.
[0034] Beneficial effects:
[0035] The present invention provides a high-strength and wear-resistant nylon material for rails. The toughening agent of the core-shell structure significantly improves the performance of the nylon material, which effectively enhances the impact resistance of the nylon material, so that it can better maintain structural integrity when subjected to external force impact. At the same time, the tensile strength is also improved, so that the nylon material can better withstand tensile stress; in addition, the improvement of wear resistance allows the nylon material to perform better in a friction environment, greatly expanding the application range of the nylon material. DETAILED DESCRIPTION
[0036] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0037] Polyamide fiber and long-chain linear polyamide were purchased from Zhejiang Huafeng New Materials Co., Ltd.; the anti-cratering agent was Dow Corning DC-57, purchased from Guangzhou Aike New Materials Trading Co., Ltd.; the flow agent was silicone masterbatch, purchased from Shanghai Yaozhongxin New Materials Technology Co., Ltd.; the nucleating agent was zinc phenylphosphonate, purchased from Hubei Xinhongli Chemical Co., Ltd.; the antioxidant was antioxidant 1010, purchased from BASF (China) Co., Ltd.
[0038] Unless otherwise specified, the chemical reagents used in the present invention are all commercially available analytically pure.
[0039] Preparation of core-shell toughening agent A:
[0040] S1: Preparation of shell material: first, add 10 g of 3-benzoyl-N-vinylpyrrolidin-2-one and 100 mL of ethyl acetate into a four-necked flask, stir in a constant temperature water bath to dissolve; after dissolution, add 5 mL of hydrogen peroxide and 0.03 g of azobisisobutyronitrile, raise the temperature to 80° C., and then react for 2 hours under a nitrogen atmosphere; after the reaction is completed, cool and filter, and place the insoluble matter in a vacuum drying oven to vacuum dry to obtain a shell material;
[0041] S2: Preparation of the core layer emulsion. First, add weighed 10g of aminoalkyl acrylate, 10g of propylene trimethoxysilane, and 0.2g of benzoyl peroxide into a four-necked flask, stir evenly, and obtain a premix for use; take another four-necked flask, add 4g of sodium dodecylbenzene sulfonate and 200mL of deionized water, stir evenly, heat to 100°C, and then slowly add the premix prepared above into the sodium dodecylbenzene sulfonate and deionized water, and keep the temperature for reaction for 4 hours; after the reaction is completed, cool and adjust the pH value to 7 to obtain the core layer emulsion;
[0042] S3: Add 5 g of the shell material prepared in step S1 into a four-necked flask, then add 20 g of the core layer emulsion prepared in step S2, 0.5 g of sodium dodecyl sulfate, and 100 mL of deionized water, and react at room temperature with stirring for 1 hour to obtain a core-shell copolymer emulsion;
[0043] S4: Add 10 mL of 0.1 mol / L sodium chloride solution to the core-shell copolymer emulsion prepared in S3, stir to break the emulsion, and then wash, separate and dry to obtain the core-shell toughening agent A.
[0044] Preparation of core-shell toughening agent B:
[0045] The difference between this preparation and the core-shell toughening agent A is that: 0.03g of azobisisobutyronitrile in step S1 is replaced by 0.05g of azobisisobutyronitrile; 0.2g of benzoyl peroxide in step S2 is replaced by 0.3g of benzoyl peroxide; 5g of shell material and 20g of core layer emulsion in step S3 are replaced by 5g of shell material and 10g of core layer emulsion respectively.
[0046] Preparation of core-shell toughening agent C:
[0047] The difference between the present preparation and the core-shell toughening agent A is that the 0.03 g of azobisisobutyronitrile in step S1 is replaced by 0.08 g of azobisisobutyronitrile.
[0048] Preparation of core-shell toughening agent D:
[0049] The difference between the present preparation and the core-shell toughening agent A is that the 0.2 g of benzoyl peroxide in step S2 is replaced by 0.5 g of benzoyl peroxide.
[0050] Preparation of core-shell toughening agent E:
[0051] The difference between the present preparation and the core-shell toughening agent A is that the 5 g shell material and 20 g core emulsion in step S3 are replaced with 5 g shell material and 5 g core emulsion in sequence.
[0052] Preparation of core-shell toughening agent F:
[0053] The difference between the present preparation and the core-shell toughening agent A is that the 5 g shell material and 20 g core layer emulsion in step S3 are replaced with 5 g shell material and 25 g core layer emulsion in sequence.
[0054] Preparation of high-strength and wear-resistant nylon materials for rails:
[0055] Polyamide fiber, long-chain linear polyamide, core-shell toughening agent, anti-shrinkage aid, flow agent, nucleating agent and antioxidant are mixed, added to the main feeding port of a twin-screw extruder, melt-mixed at 250° C. Glass fiber is added to the side feeding port of the twin-screw extruder, mixed at 280° C. for 10 minutes, and extruded into granules to obtain the high-strength, toughness and wear-resistant nylon material for rails.
[0056] Examples 1 to 7
[0057] According to the above-mentioned preparation method of high-strength, toughness and wear-resistant nylon material for rails, Table 1 is a list of ingredients of high-strength, toughness and wear-resistant nylon material for rails of Examples 1 to 7 in percentage.
[0058] Table 1
[0059]
[0060] Comparative Examples 1 to 4
[0061] Comparative Examples 1 to 4 were prepared according to the above method for preparing high-strength, toughness, and wear-resistant nylon materials for rails. Table 2 is a list of ingredients of the high-strength, toughness, and wear-resistant nylon materials for rails of Comparative Examples 1 to 4 in percentage.
[0062] Table 2
[0063]
[0064]
[0065] Performance test: The nylon materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were prepared into strip samples of 2×5×10 cm for use in the following tests.
[0066] 1. Impact resistance test:
[0067] Charpy Impact Test: According to the standard (such as ISO 180), a 2×5×10 cm strip specimen is prepared into a specimen with an A-type notch. The specimen is placed on a support table and a pendulum impact tester is used to release the pendulum to impact the specimen and measure the impact energy absorbed by the specimen.
[0068] 2. Tensile strength test:
[0069] According to the standard (such as ISO 527), the prepared 2×5×10 cm long strip specimen is stretched using a universal material testing machine at a stretching speed of 1 cm per minute until the specimen breaks. The force and displacement data during the stretching process are obtained to calculate the tensile strength.
[0070] 3. Wear resistance test:
[0071] Taber Abrasion Test: According to the standard (such as ASTM D4060), a 2×5×10cm sample is mounted on a rotating platform, and a grinding wheel is used to rub the sample. The wear resistance is evaluated by measuring the mass loss or thickness loss of the sample. Reciprocating Friction and Wear Test: The sample and the friction pair are reciprocated for 100 times under a load of 5N, a speed of 50mm / min and a stroke of 400mm, and the wear resistance is evaluated by measuring parameters such as the wear rate.
[0072] Table 3: Test results
[0073] Material <![CDATA[Notched impact strength kJ / m 3 > Tensile strength / MPa Wear rate / % Example 1 19 195 2 Example 2 20 196 2 Example 3 20 189 2 Example 4 17 180 5 Example 5 16 175 5 Example 6 12 160 6 Example 7 13 163 6 Comparative Example 1 5 102 8 Comparative Example 2 5 95 8 Comparative Example 3 6 120 4 Comparative Example 4 16 154 4
[0074] From the above data, it can be seen that the high-strength and wear-resistant nylon materials for rails of Examples 1 to 3 have strong impact resistance, tensile strength and wear resistance; from the comparison between Example 4 and Example 2, it can be seen that adjusting the shell material of the core-shell toughening agent and the use of the initiator dosage will make the impact resistance, tensile strength and wear resistance of the prepared high-strength and wear-resistant nylon material for rails worse; from the comparison between Example 5 and Example 2, it can be seen that adjusting the amount of benzoyl peroxide used when preparing the core layer emulsion with the core-shell toughening agent will make the impact resistance, tensile strength and wear resistance of the prepared high-strength and wear-resistant nylon material for rails worse; from the comparison between Examples 6 to 7 and Example 2, it can be seen that unreasonable control of the mass ratio of the shell material and the core layer emulsion of the raw materials for preparing the core-shell toughening agent will make the impact resistance, tensile strength and wear resistance of the prepared high-strength and wear-resistant nylon material for rails worse; from the comparison between Comparative Example 1 and Example 2, it can be seen that without adding polyamide fiber (PA66), This results in the prepared high-strength and tough wear-resistant nylon material for rails having poor impact resistance, tensile strength and wear resistance; from the comparison between Comparative Example 2 and Example 2, it can be seen that when long-chain linear polyamide (PA12) is not added, the impact resistance, tensile strength and wear resistance of the prepared high-strength and tough wear-resistant nylon material for rails will be poor; from the comparison between Comparative Example 3 and Example 2, it can be seen that when no core-shell toughening agent is added and the flow agent Dow Corning DC-57 is added, the impact resistance, tensile strength and wear resistance of the prepared high-strength and tough wear-resistant nylon material for rails are poor, and the expected effect cannot be achieved. From the comparison between Comparative Example 3 and Example 2, it can be seen that when the flow agent Dow Corning DC-57 is not added and the amount of core-shell toughening agent is increased, the impact resistance, tensile strength and wear resistance of the prepared high-strength and tough wear-resistant nylon material for rails are also poor. The core-shell toughening agent and the flow agent Dow Corning DC-57 have a synergistic effect in improving the friction of the high-strength and tough wear-resistant nylon material for rails.
[0075] The present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A high-strength and wear-resistant nylon material for rails, characterized in that: The raw materials of the high-strength and wear-resistant nylon material for the rails include, by weight percentage, 30-50% polyamide fiber, 10-18% long-chain linear polyamide, 30-40% glass fiber, 2-8% core-shell toughening agent, 1-3% anti-shrinkage auxiliary agent, 1-2% flow agent, 0.5-1.5% nucleating agent, and 0.1-0.5% antioxidant.
2. The high-strength and wear-resistant nylon material for rails according to claim 1, characterized in that: The raw materials for preparing the core-shell toughening agent include a shell material and a core emulsion; the shell material is polymerized by 3-benzoyl-N-vinylpyrrolidone under the action of an initiator; the raw materials for preparing the core emulsion include aminoalkyl acrylate, acryltrimethoxysilane, benzoyl peroxide, an organic additive, and deionized water.
3. The high-strength and wear-resistant nylon material for rails according to claim 2, characterized in that: The preparation of the shell material comprises the following steps: S1: Add 3-benzoyl-N-vinylpyrrolidin-2-one and a certain amount of ethyl acetate into a four-necked flask, and stir in a constant temperature water bath to dissolve them; S2: After dissolution, hydrogen peroxide and an initiator are added, the temperature is raised to 50-80°C, and then the reaction is carried out under a nitrogen atmosphere for 2-4 hours; S3: After the reaction is completed, the reaction mixture is cooled and filtered, and the insoluble matter is placed in a vacuum drying oven for vacuum drying to obtain a shell material.
4. The high-strength and wear-resistant nylon material for rails according to claim 3, characterized in that: The added amount of the initiator is 0.3-0.5% of the mass of 3-benzoyl-N-vinylpyrrolidone-2-one; and the initiator is azobisisobutyronitrile.
5. The high-toughness and wear-resistant nylon material for rails according to claim 2, characterized in that: The preparation of the nuclear layer emulsion comprises the following steps: S1: Add weighed aminoalkyl acrylate, acryltrimethoxysilane and benzoyl peroxide into a four-necked flask, stir evenly to obtain a premix for later use; S2: Take another four-necked flask, add an organic additive, stir evenly, heat to 90°C to 100°C, then slowly add the premix prepared in step S1 to the organic additive and deionized water, and keep the temperature to react for 2 to 4 hours; S3: After the reaction is completed, cool the mixture and adjust the pH value to 6-7 to obtain a core layer emulsion.
6. The high-strength and wear-resistant nylon material for rails according to claim 5, characterized in that: The added amount of benzoyl peroxide is 1-1.5% of the total mass of aminoalkyl acrylate and acryltrimethoxysilane.
7. The high-strength and wear-resistant nylon material for rails according to claim 5, characterized in that: The amount of the organic auxiliary agent is 20-40% of the total mass of aminoalkyl acrylate and acryltrimethoxysilane; and the organic auxiliary agent is sodium dodecylbenzene sulfonate.
8. The high-strength and wear-resistant nylon material for rails according to claim 2, characterized in that: The preparation of the core-shell toughening agent comprises the following steps: S1: adding the shell layer material into a four-necked flask, and then adding the core layer emulsion, sodium dodecyl sulfate, and deionized water, stirring and reacting at room temperature for 1 to 2 hours to obtain a core-shell copolymer emulsion; S2: Add sodium chloride to the core-shell copolymer emulsion prepared in S1, stir and demulsify, then wash, separate and dry to obtain a core-shell toughening agent.
9. The high-strength and wear-resistant nylon material for rails according to claim 2 or 8, characterized in that: The mass ratio of the shell layer material to the core layer emulsion is 1:2-4.
10. The method for preparing the high-toughness and wear-resistant nylon material for rails according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing polyamide fiber, long-chain linear polyamide, core-shell toughening agent, anti-shrinkage cavity additive, flow agent, nucleating agent and antioxidant, adding the mixture to the main feeding port of a twin-screw extruder, melting and mixing, adding glass fiber to the side feeding port of the twin-screw extruder, mixing, extruding and granulating, and obtaining the high-strength and wear-resistant nylon material for rails.
Citation Information
Patent Citations
Method for reinforcing and toughening PA6 alloy
CN108395694A
High-toughness good-moldability nylon composite material and preparation method thereof
CN109722012A
High-toughness flame-retardant nylon material and preparation method thereof
CN109825072A
Anti-fatigue low-temperature-resistant nylon composite material as well as preparation method and application thereof
CN117659696A
Toughened polyamide blends
US4478978A
Cited By
Polyamide resin composition as well as preparation method and application thereof
CN121592170A